Odpowiedzi

2010-02-03T20:46:33+01:00
4y= 3x-4
2x=-3(y-5)-1

4y=3x-4
2x=-3y+15-1

-3x+4y=-4
2x=-3y+14 |:2

-3x+4y=-4
x=-3/2y+7

-3(-3/2y+7)+4y=-4
x=-3/2y+7

9/2y-21+4y=-4
x=-3/2y+7

4,5y+4y=-4+21
x=-3/2y+7

8,5y=17 |:8,5
x=-3/2y+7

y=2
x=-3/2*2+7

x=-3+7
y=2

x=4
y=2
2010-02-03T20:52:58+01:00
4y=3x-4/*3
2x=-3y+15-1/*(-4)

12y=9x-12
-8x=+12y-60+4

12y-9x=-12
-12y-8x--41

-17x=-56/:(-17)
12y-9x=-12

x=około3
12y-9*3=-12

x=3
12y=39
x=3
y=3.25



2010-02-03T21:00:46+01:00
4y - 3x = -4
2x = 3y - 15 - 1

4y - 3x = -4
2x - 3y = -16

-3x + 4y = -4 / * 2
2x - 3y = -16 / *3

-6x + 8y = -8
6x - 9y = -48

-y = -56 / * -1
y = 56

6x - 9*56 = -48
6x = 504 - 48

6x = 456 / :6
x = 76

y = 56
x = 76